Autopercepción sobre la comunicación asertiva en estudiantes con discapacidad intelectual (Investigaciones) - Belmonte, María Luisa (2024)
Communication is the main tool for adequate socialization. Assertive communication favors interpersonal relationships, life satisfaction, self-confidence, expressiveness and spontaneity, which are sometimes so difficult to achieve for people with intellectual disabilities. This study, through the application of the Assertiveness Questionnaire of the mental health project “Promoting the healthy adaptation of our adolescents”, to 19 students with intellectual disabilities from the Todos Somos Campus training program, of the University of Murcia, has investigated the level of assertiveness of these young people and their self-perception of their communication style (assertive, passive or aggressive). The results show that students present a medium level of assertiveness, with differences existing between those who identify with an assertive communication style and those who believe they have passive communication. All of this only continues to demonstrate the importance of training in assertiveness and communication skills, given that, together with others, they form the pillars of every person’s social skills, directly impacting their quality of life.